The collaborative approach in content and language integrated learning - Carrió Pastor, María Luisa; Perry, David (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2010)
The specific knowledge that can be found in web sites provides a source of information which should be used by language teachers and content teachers to teach students both subject matter and language at the same time. In this paper, we describe the methodology followed in a still ongoing project in which content teachers and language teachers collaborated in order to design online teaching-learning materials which integrated subject matter and language tasks. We explain the criteria followed in designing and evaluating the different activities proposed in order to connect two subjects that have been traditionally taught separately and we provide some examples. Our main conclusion is that language teaching and content teaching can be successfully integrated. The activities proposed proved to be encouraging for both content learning and second language learning, reinforcing students' self-steem and collaborative behaviour in the classroom and online.